Tony Atkinson's New Book, Measuring Poverty around the World: Some Further Reflections - Andrea Brandolini; John Micklewright (Institute of Labor Economics (IZA), 2020)
A new book on measuring global poverty by the late Tony Atkinson was published in 2019 by Princeton University Press. We describe how we edited the incomplete manuscript that Atkinson left at his death, the additions we made (which include afterwords by François Bourguignon and Nick Stern), and the content and structure of the book. We then discuss what we believe Atkinson was trying to achieve, emphasising both the important insights of the book and where the gaps remain. We also review parallel developments in the World Bank's measurement of global poverty that were stimulated by the report of the Commission on Global Poverty, written by Atkinson, from which this book was developed. The new book is more than four hundred published pages. It remains unfinished yet it is a masterly guide to the nuances of poverty measurement and an invaluable source for future research.
Keywords: C80; I32; 330; global poverty; income; consumption; multidimensional poverty; cosmopolitanism